Assessing the neurological impact of vitamin B12 deficiency among the population of Riyadh, Saudi Arabia - Bin Abdulrahman, Khalid A.; Alshehri, Abdulelah F.; Almutairi, Faisal Marzouq; Almahyawi, Faisal Ali; Alzahrani, Rayan Saleh; Al-Ahmari, Osama Thamer; Alshammari, Khalid; Aljuhani, Turki Ahmed; Alkadi, Yazeed Yahya; Alisi, Mohammed Atiah (Frontiers in Nutrition, 2025)
BackgroundVitamin B12 (cobalamin) deficiency can cause anemia, peripheral neuropathy, visual impairment and irreversible neurological damage. Little is known about public awareness of these neurological effects in Saudi Arabia. This study assessed awareness of the neurological impact of vitamin B12 deficiency among adults in Riyadh, Saudi Arabia.MethodsWe conducted a population-based cross-sectional survey in Riyadh between March and April 2024. Adults aged ≥18 years were recruited via social media. Individuals affiliated with the health sector were excluded to reduce bias. A validated questionnaire assessed sociodemographics, awareness of vitamin B12, dietary sources, deficiency symptoms and prevention. Descriptive statistics and chi-square tests were used (P < 0.05).ResultsOf 1,337 participants, 23 were excluded, leaving 1,314 respondents; 62.3% were female. Most (65.6%) recognized the importance of vitamin B12, 38.7% identified a dietary source, and 29.9% used supplements. Awareness of the neurological consequences of deficiency was reported by 63.4%. Women showed greater knowledge than men (P < 0.001), and employed participants or those in “other” occupations were more aware than students.ConclusionOverall awareness of vitamin B12 and its neurological consequences was moderate. However, knowledge of dietary sources and prevention strategies was limited, and misperceptions (e.g., fruits and vegetables as sources) were common. Targeted public-health education and nutritional counseling are needed to address these gaps.